Diminished ketone interconversion, hepatic TCA cycle flux, and glucose production in D-β-hydroxybutyrate dehydrogenase hepatocyte-deficient mice - David B. Stagg; Jacob R. Gillingham; Alisa B. Nelson; Justin E. Lengfeld; D. André d'Avignon; Patrycja Puchalska; Peter A. Crawford (Elsevier, 2021)
Objective: Throughout the last decade, interest has intensified in intermittent fasting, ketogenic diets, and exogenous ketone therapies as prospective health-promoting, therapeutic, and performance-enhancing agents. However, the regulatory roles of ketogenesis and ketone metabolism on liver homeostasis remain unclear. Therefore, we sought to develop a better understanding of the metabolic consequences of hepatic ketone body metabolism by focusing on the redox-dependent interconversion of acetoacetate (AcAc) and D-β-hydroxybutyrate (D-βOHB). Methods: Using targeted and isotope tracing high-resolution liquid chromatography-mass spectrometry, dual stable isotope tracer nuclear magnetic resonance spectroscopy-based metabolic flux modeling, and complementary physiological approaches in novel cell type-specific knockout mice, we quantified the roles of hepatocyte D-β-hydroxybutyrate dehydrogenase (BDH1), a mitochondrial enzyme required for NAD+/NADH-dependent oxidation/reduction of ketone bodies. Results: Exogenously administered AcAc is reduced to D-βOHB, which increases hepatic NAD+/NADH ratio and reflects hepatic BDH1 activity. Livers of hepatocyte-specific BDH1-deficient mice did not produce D-βOHB, but owing to extrahepatic BDH1, these mice nonetheless remained capable of AcAc/D-βOHB interconversion. Compared to littermate controls, hepatocyte-specific BDH1 deficient mice exhibited diminished liver tricarboxylic acid (TCA) cycle flux and impaired gluconeogenesis, but normal hepatic energy charge overall. Glycemic recovery after acute insulin challenge was impaired in knockout mice, but they were not more susceptible to starvation-induced hypoglycemia. Conclusions: Ketone bodies influence liver homeostasis. While liver BDH1 is not required for whole body equilibration of AcAc and D-βOHB, loss of the ability to interconvert these ketone bodies in hepatocytes results in impaired TCA cycle flux and glucose production. Therefore, through oxidation/reduction of ketone bodies, BDH1 is a significant contributor to hepatic mitochondrial redox, liver physiology, and organism-wide ketone body homeostasis.